Indonesia sebagai Negara Maritim: Tinjauan Historis Perkembangan Pelayaran Nusantara - Yohanis Kristianus Tampani; Augusta De Jesus Magalhaes; Delfiana Klaran Nahak; Efantri Manhitu; Maria Yulinda Luruk; Yanuarius Lutan; Angela Abi (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
This study aims to describe and analyze the historical development of maritime navigation in the Indonesian archipelago (Nusantara) and its relevance to Indonesia's identity as a maritime nation. The study employs a literature review method by collecting and analyzing data from various primary and secondary sources. The results indicate that Indonesia has a long and rich maritime history, as evidenced by the dominance of maritime kingdoms such as Sriwijaya and Majapahit, which controlled major sea trade routes and built extensive international networks. The development of Nusantara navigation was also influenced by the introduction of various maritime technologies, the spread of religion through sea routes, and ultimately the impact of European colonialism which disrupted traditional maritime trade systems. In the modern era, Indonesia's maritime identity has been revitalized through the Sea Toll program and the Global Maritime Fulcrum vision. This study concludes that an understanding of the historical development of Nusantara navigation is essential as a foundation for building a strong, sovereign, and prosperous maritime Indonesia.